(untitled) (The Saraswati Review, 2024)
Magar is one of the indigenous nationalities of Nepal having their distinct cultural heritage, linguistic identities and social values. In this study it analyzes the introduction of Magar and their intangible cultural heritage that has been practiced by the Magar living in Bhimad municipality of Tanahun district. The main objective of this study is highlighting the major intangible cultural heritage of Magar such as religion, language, traditional belief and practice. The study only focuses on language religion and traditional practice of Magar in term of intangible cultural heritage. In this regard the study followed qualitative research design. Both primary and secondary source of the data were used. The study has been concluded on the basis of primary data collected from the field from the analysis of the opinion and perception of the respondents. The Magar has rich intangible cultural heritage that has been practicing in the study area, however, modernization and influences of different religions, like Buddhism, Christianity and create problems in the continuation of the traditional cultural heritage of the Magar living in the study area.